The spiritual and psychosocial gender specific stories of adolescent orphans affected by HIV and Aids in the absence of a father figure : a postfoundational practical theological approach - Muller, Julian C. (University of Pretoria, 2013)
Thesis (PhD (Pastoral Family Therapy))--University of Pretoria, 2010.